BEZEK ARTÍNDAǴÍ HIKMET: QARAQALPAQ MILLIY NAǴÍSLARÍNÍŃ SÍRLÍ DÚNYASÍ - Amanbaev, M. (SCIENCE and SOCIETY, 2025)
The article examines the symbolic content of national ornaments, especially the symbolic content of floral patterns, the meaning of beauty. In addition, a brief description of the history of paftern is given, along with examples from scientists who have achieved scientific results in this field. The article reveals that national beauty is not only an ornament, but also a spiritual heritage.